Escoamento bifásico em meios porosos: aplicações na recuperação de óleo e infiltração de fluidos adesivos - Oliveira, Claudio Lucas Nunes de (2009)
The fluids displacement in porous media has been subject in researches with great scientific and technologic interesting due to its close connection to industry applications, like oil recovery problem, groundwater studies etc. In this thesis, we have investigated through numerical simulations three two-phase flow problems. The first one, is about the secondary oil recovery method, which consist to push the oil using the injection of water; the second case, treats of the tertiary oil recovery method, where the oil viscosity is decreased by the increasing of the temperature; and the last one, is an interfacial hardness model to simulate the glue penetration in porous media. In the first part, we study the behavior of the oil production rate in an isothermal and two-dimensional reservoir field. Water is pushed from an injection to a production well, separated by a distance r. This corresponds to the secondary recovery method in oil reservoirs. We then investigate through direct numerical calculation using the commercial reservoir field simulator STARS of CMG (Computer Modelling Group) the influence of the viscosity ratio (m = moil/mwater) on the oil production (C(t)) when m ≥ 1. We keep m constant through simulation. We first consider a macroscopically disordered and homogeneous reservoir. In this case, all the geometry is accessible to the fluids, but the porosity varies randomly in space. The results show two power law regimes in the oil production curves, with exponent -1/3 and -5/2. We also study the behavior of inhomogeneous system with a percolation-like reservoir geometry. We see in this case a power law behavior with exponent -0.8 in C(t) curves. We verify that the breakthrough time carries units of r 1.8 m1/4 in the homogeneous case and r m1/5 in the inhomogeneous one. When the kind of oil is heavy, tertiaries methods are necessary to improve the recovery. One of the most used techniques is the Steam Injection, where a hot fluid (usually, water or steam) is injected into the reservoir to decrease the oil viscosity. In order to make those studies we consider a microscopic approximation of the medium. The oil viscosity is dependent on temperature according the following function, exp(B/T), where B is a physico-chemical parameter which define the kind of oil, and T is the temperature. A gradient of temperature, ∆T, is applied crossing the medium in the same direction of the injection. Initially, the porous medium is saturated with oil and, then, another fluid is injected. We have considered two cases of injection. The first one, the viscosity of the invading fluid is constant (the viscosity ratio is, then, finite) and the second one, the invading fluid is inviscid (infinite viscosity ratio). Our results show that the recovery efficiency of the oil can increase substantially with the ∆T. We show, also, that the percentage of the oil recovery decreases with B for the finite viscosity ratio case, but the opposite behavior for the other case. In the last part, we propose an Invasion Percolation modified model to simulate the penetration of a fluid into another with hardening interface. Initially, the capillary pressure of each site in the lattice is randomly chosen between 0 and 1, and then, the hardness effect by contact with the defending phase is obtained by increasing the pressure of those sites at interface. The most time exposition a site has the greatest is its pressure value. During this exposition, if a site has pressure greater or equal to 1, that site becomes a pine and cannot be invaded anymore. That represents a glue penetrating into a porous medium where it becomes hard due to exposition with the air. We also consider three different regimes of the displacement according the Bond number, Bo > 0, Bo = 0 and Bo < 0. We have analyzed the influence of that hardness effect in those regimes. We see that, besides the patterns change with this effect, the average behavior do not affect much.